Radiological Spectrum of Pseudoangiomatous Stromal Hyperplasia of Breast—A Case Series - Parameswaran, Prathiba Rajalakshmi; Renganathan, Rupa; Subramaniam, Prema; Thakur, Vinita (Indian Journal of Radiology and Imaging, 2022)
Pseudoangiomatous stromal hyperplasia (PASH) is a benign mesenchymal tumor-like lesion of the breast. It is commonly seen as incidental background changes of the intralobular stroma in biopsy specimens performed for other breast lesions. Less frequently, it presents as a nodular form that has a benign morphology on imaging, mimicking fibroadenoma or as a diffuse form causing progressive massive gigantomastia. Diagnosis is established by biopsy. Knowledge of the imaging appearance of PASH not only facilitates proper assessment of radiopathological correlation but also helps in deciding further management of these lesions. Occasionally, nodular PASH may have a suspicious appearance on imaging wherein excision biopsy is indicated to exclude a coexisting carcinoma.
Keywords: pseudoangiomatous stromal hyperplasia; nodular form; diffuse form; incidental PASH changes